(untitled) (Journal of the College of Education for Women, 2019)
The good and homogenous lighting is important in resolution imageand obtaining high contrast in visual image. In this research, three texts havewritten on Wight board and they were picturing by digital camera on differentdistances between the text and digital camera depends on fluorescent lightingusing Sobol Operator image to obtain edges for three image text image. Themean (statistical and diagonal) contrast has been determined to the text image in edges area. The research notes that the mean (statistical and diagonal) contrast of text images decreases with increases the distancebetween the camera and the board.